DAYA SAING DAN POTENSI PENGEMBANGAN EKSPOR PRODUK KELAPA PARUT KERING KE ENAM NEGARA UNI EROPA - Ananda Azhar; Fathya Medy; Dewi Anggraini; Tiara Yoda; Oryzasativa Dewi (Universitas Sains dan Teknologi Komputer, 2023)
The European Union is the world's largest importer of desiccated coconut products with the six main import destinations being the Netherlands, Germany, the UK, Poland, Belgium and France. Despite ups and downs in the last five years, Indonesia's exports of desiccated coconut products have increased again in 2021. To determine the competitiveness and development potential of dessicated coconut products to six major markets in the European Union, this study used the RCA and EPD methods. The results show that all six countries are highly competitive for Indonesian dessicated coconut exports. France is an optimistic market for export development. Potential markets for export development are the Netherlands, Germany, the UK and Belgium.